2009
DOI: 10.1021/je8003222
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Routes and Metastability of α-Calcium Sulfate Hemihydrate in Potassium Chloride Solutions under Atmospheric Pressure

Abstract: The phase transitions of α-calcium sulfate hemihydrate (α-HH) in KCl solutions were studied at (80 to 105) °C under atmospheric pressure in an attempt to estimate the metastability of α-HH and to sketch out the routes for α-HH’s hydration, dehydration, or recrystallization. The crystal water content and morphology of the product during the reaction period were comprehensively examined. It was found that the metastability of α-HH heavily relied on KCl concentration and temperature. The phase transition of α-HH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…Despite its weaker intensity in comparison to that of the commercial product the characteristic exothermic peak in the DSC trace that distinguishes the alpha and beta HH varieties [40][41][42] can be clearly seen. In typical batch reactor growth rate studies, the change in solute concentration is used to derive the growth rate.…”
Section: Nearly Constant Supersaturation Crystallization Of α-Hhmentioning
confidence: 94%
“…Despite its weaker intensity in comparison to that of the commercial product the characteristic exothermic peak in the DSC trace that distinguishes the alpha and beta HH varieties [40][41][42] can be clearly seen. In typical batch reactor growth rate studies, the change in solute concentration is used to derive the growth rate.…”
Section: Nearly Constant Supersaturation Crystallization Of α-Hhmentioning
confidence: 94%
“…[1][2][3][4], showing excellent thermal stability and mechanical strength [5][6][7]. Calcium sulfate whiskers can be produced by preparing α-CaSO 4 ·0.5H 2 O whiskers through hydrothermal, acidification, reverse micro-emulsion, and microwave-assisted approaches [8][9][10][11][12][13] followed by calcination of the α-CaSO 4 ·0.5H 2 O whiskers above 600 • C [14,15]. Compared with the other methods, the hydrothermal route was widely used thanks to its moderate conditions and easily controlled parameters and whisker properties [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that HH crystal consists of corner-sharing SO 4 − and CaO 8 − polyhedral chains, which are hexagonally arranged and form a three-dimensional framework with continuous channels parallel to [001] direction. These channels have a diameter of about 4.5 Å and are partially filled with H 2 O molecules [10] .…”
Section: Morphologies Of the Surface Of α-Hh Crystalsmentioning
confidence: 99%
“…FGD gypsum thereby produced can amount up to 20 million tons per year since 2007. Besides utilizing FGD gypsum in wallboards and concrete blocks manufacturing, or in cement as an additive [3] , preparation of α-HH is one of the promising ways for FGD gypsum utilization, because this high value cementitious material has wide application areas for its superior workability and high strength [4,5] .…”
Section: Introductionmentioning
confidence: 99%